SCAFFOLD DARI BOVINE HYDROXYAPATITE DENGAN POLY VYNIALCHOHOL COATING - Alva Edy Tontowi, Punto Dewo, Endang Tri Wahyuni, dan Joko Triyono (Universitas Gadjah Mada, 2012)
In Indonesia, it is about 40% patients with hard tissue defect due to ostheoporosis, cancer or accidents and therest are defect since they have born.For many years, efforts for recovering have been done by transplantation orimplantation methods.Transplantation is more appropriate butit is not sustain because of limited donor, whileimplantation using synthetic materials such as bioceramics scaffoldis expensive due to import and the scaffold iseasier to break which does not match to the medical requirements.The research therefore has been addressed to thisissue. Local bovine hydroxyapatite (bHA)scaffold has been used as thebase material and poly vynilalchohol (PVA)as a coating material.The bHA scaffold was prepared by cutting a fresh bovine bone in the size of 5mmx5mmx5mmand boil it in a distilled water to remove its organic material. It was then heated up at 900 oC for 2 hours infurnace to obtain bovine hydroxyapatite scaffold (bHA). Coating process has been carried out by dip coating of thebHAscaffold in PVA solution.